Role of Anti-Vascular Endothelial Growth Factor (Anti-VEGF) in the Treatment of Retinopathy of Prematurity: A Narrative Review in the Context of Middle-Income Countries - Dogra MR; Vinekar A (Dove Medical Press, 2023)
Mangat Ram Dogra,1 Anand Vinekar2 1Grewal Eye Institute, Chandigarh, India; 2Narayana Nethralaya Eye Institute, Bangalore, IndiaCorrespondence: Anand Vinekar, Narayana Nethralaya Eye Institute, Bangalore, India, Email anandvinekar@yahoo.comAbstract: The rise in preterm births and higher survival rates of premature infants have led to a global increase in retinopathy of prematurity (ROP), a vasoproliferative retinal disorder common in premature infants. ROP is one of the leading causes of childhood blindness. Clinical manifestation of ROP ranges from mild abnormal retinal neovascularization to bilateral retinal detachment and vision loss. The incidence of ROP is higher in middle income countries, including India, which has the highest number of global preterm births. Low birth weight and low gestational age are the primary risk factors for ROP; however, anemia, cardiac defects, blood transfusion, apnea, sepsis, respiratory distress syndrome, high exposure to oxygen and poor postnatal weight gain may also contribute to its development. India has stringent ROP screening guidelines revised in 2018, and screening of infants with either birth weight < 2000 grams or gestational age < 34 weeks is mandated. With an improved understanding of the pathogenesis of ROP in the past decades and advances in clinical research, treatment for ROP has evolved from cryotherapy to laser retinal ablation. Most recently, anti-vascular endothelial growth factor (anti-VEGF) drugs have emerged as a favorable treatment option for zone-I and II ROP. This article reviews the current approaches for ROP treatment in India with a particular focus on anti-VEGF drugs. The article also integrates the understanding of safety and risk-benefit evaluation of the current approaches in ROP management. The review concluded that there is a need to increase the ROP screening not only for preterm and low birth weight but also for optimal gestational age infants with healthy birth weight. Anti-VEGF therapies have shown improved efficacy, although studies are required to establish the long-term safety.Keywords: retinal disorder, childhood blindness, ROP management, anti-VEGF therapy, laser retinal ablation